2014
DOI: 10.2147/ott.s65367
|View full text |Cite
|
Sign up to set email alerts
|

Silencing B7-H1 enhances the anti-tumor effect of bladder cancer antigen-loaded dendritic cell vaccine in vitro

Abstract: ObjectiveThe aim of this study was to examine whether short hairpin RNA (shRNA) expressing lentiviral particles targeting B7-H1 infection could result in B7-H1 knockdown on dendritic cells (DCs) and to investigate whether B7-H1 silencing could augment the immune function of DCs and further elicit a more potent anti-tumor immune effect against bladder cancer cells in vitro.MethodsMonocyte-derived DCs, which were generated from peripheral blood mononuclear cells, were infected by a recombinant lentivirus contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Advanced clinical trials with PD-1 and PD-L1 antibodies show very promising results in preventing axis signaling in non-small cell lung cancer, indicating the potential that blocking this pathway enhances anti-tumor immunity ( 112 ). Silencing of PD-L1, on its own ( 113 ) or in combination with its phagocyte-restricted relative PD-L2 ( 114 ), shows augmented ex vivo TAA-specific CTL responses, which is also confirmed in vivo ( 115 ). Moreover, combined silencing of PD-L1 and IL-10 in DC vaccination showed even stronger induction of anti-tumor responses in vitro and in vivo ( 106 ) indicating the potential of combining DC modifications in maximizing anti-tumor responses.…”
Section: Interferance With Co-inhibitory and Immunosuppressive Pathwamentioning
confidence: 81%
“…Advanced clinical trials with PD-1 and PD-L1 antibodies show very promising results in preventing axis signaling in non-small cell lung cancer, indicating the potential that blocking this pathway enhances anti-tumor immunity ( 112 ). Silencing of PD-L1, on its own ( 113 ) or in combination with its phagocyte-restricted relative PD-L2 ( 114 ), shows augmented ex vivo TAA-specific CTL responses, which is also confirmed in vivo ( 115 ). Moreover, combined silencing of PD-L1 and IL-10 in DC vaccination showed even stronger induction of anti-tumor responses in vitro and in vivo ( 106 ) indicating the potential of combining DC modifications in maximizing anti-tumor responses.…”
Section: Interferance With Co-inhibitory and Immunosuppressive Pathwamentioning
confidence: 81%
“…The possibility of such inconclusive studies have been checked so far because of a shortage of convincing evidence. 40 , 41 Maybe future work will be influenced by the decrease of match detection. By adding sampling rate and specific groups to prove gene, polymorphism and environmental factor will have an influence on morbidity of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the PD-1/PD-L pathway, silencing of PD-L1 and/or PD-L2 in DCs has been evaluated with different RNAi introduction techniques, including viral transduction and non-integrating electrotransfection, lipid nanoparticle transfection, and the cGMP-compliant transfection reagent SAINT-RED ( 77 , 138 , 141 , 143 , 144 ). Preclinical data demonstrated that PD-L-silenced DCs could (1) increase expansion, promote pro-inflammatory cytokine secretion and degranulation, and augment antitumor function of antigen-specific CD8 + T cells in human in vitro models ( 138 , 140 , 142 ) and (2) induce significant antitumor immunity in vivo in different malignant mouse models ( 139 , 141 ). Alternatively, in situ PD-L silencing can also be achieved through the use of small molecules.…”
Section: Strategies To Leverage DC Immunopotency By Interceding Pd-1/mentioning
confidence: 99%